DNA-BASED NANOPARTICLES: A PLATFORM TO PROVIDE HIGH EN-CAPSULATION, STABILITY AND PROLONGED RELEASE FOR DOXORUBICIN - Maria Gabriela Villamizar Sarmiento; Estefanía Elgueta; Andrew F.G. Quest; Felipe A. Oyarzún-Ampuero; Mauricio Báez; Ignacio Moreno-Villoslada (Journal of the Chilean Chemical Society, 2025)
Abstract: Background/Objectives: Doxorubicin (DOX) is a potent drug for cancer treatment but presents limitations for encapsulation and prolonged release. Nanoparticles (NPs) are an alternative to mitigate these issues; nevertheless synthetic methods are often complex and inefficient. This study focus in the development of DNA-based NPs, using DNA as unique excipient allowing ionic and aromatic interactions with DOX. Methods: The NPs formation consists in the mixture of DNA and DOX in water (aromatic and non-aromatic polyelectrolytes were used as positive and negative controls, respectively). UV-visible and fluorescence spectroscopy were used to corroborate the DOX/DNA interactions and to elucidate the mode of binding. Turbidimetry, dynamic light scattering, laser Doppler anemometry, nanoparticle tracking analyses, ultrafiltration, and scanning transmission electron microcopy were used to characterize the efficiency of the process and the morphology of DOX/DNA NPs. In vitro release, viability in non-cancerous cells and stability tests were conducted to assess the release profile and safety of the NPs. Results: DOX associates with DNA through ionic and aromatic interactions forming spherical NPs (115-220 nm, polidispersity 0.3-0.5, ~-27 mV, 8-13x1011 NPs/mL) with DOX association efficiency of 66-80% and loading in the range of 40-60%. DOX/DNA NPs exhibited prolonged release (55% in 12 days), stability at storage (at least 8 weeks) and does not provide toxicity in non-cancerous cells. Conclusions: We provide a simple strategy to entrap and release DOX in the form of NPs in DNA based platforms. This strategy could be used for other aromatic anticancer drug and selecting DNA sequences able to support anticancer activity.